Turbine wheel fracture analysis of Jet Fuel Starter (JFS) engine used on F16 military aircraft. (October 2021) - Balli, Ozgur
Highlights: Turbine wheel fracture of Jet Fuel Starter engine was analyzed. Cracks, material loss, metal deposit and pitting were observed on turbine wheel. Cracks were initiated from multiple points assisted by thermal fatigue. Repeated loads enhanced the cracks from blade edge to center. Remaining crass-section did not endurance to overload. Abstract: This study presents the metallurgical analysis results of fracture failure occurred on the turbine wheel of Jet Fuel Starter (JFS) used on F16 Military Aircraft. A lot of cracks, main material loss, metal deposit and pitting were observed on turbine wheel. When the investigable turbine wheel blade surface was examined, the cracks on blade surfaces were started from multiple points assisted by thermal fatigue. Then, the repeated loads enhanced the cracks from blade edge to center. Finally, the residual cross-section surface was completely broken off because the residual cross-section surface did not endure the overload effects overcoming on it. The imbalance malfunction took place in JFS after the turbine wheel blades were broken. In this situation, the compressor wheel rubbed to the casing, than some damages occurred on the casing surface and compressor wheel blades as a result of rubbing, and the JFS rear bearing disintegrated.